IMPROVING VOCABULARY USING INITIAL LETTERS GAMEAT THE FOURTH GRADE OF SDN HARAPAN 01 CIMAHI - Siti Solah Heha; Deshra Lies Nurafifah; Maudyna Rossa Pradita (PROJECT (Professional Journal of English Education), 2018)
Improving Vocabulary Using Initial Letters Game at The Fourth Grade of SDN Harapan 01 Cimahi. This research conducted to find out students' vocabulary achievement through initial letter game. The subjects of this research were class IV of SDN Harapan 1 Cimahi. The data collected using Classroom Action Researchincluding two cycles and each cycle consist of pretest and the post-test of vocabulary tests. After the implementation of initial letter game activities in first cycle and second cycle, the students’ vocabulary score is getting better. It can be seen from the result of the students’ post-test average score,cycle 1 was 67,50 and cycle 2was 85,2. The result showed thatInitial letters game can improved the students' vocabulary and can motivated students for learn English